2019
DOI: 10.1002/andp.201800453
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Accurate Refractive Index Sensor with Two Operation Modes Based on Photonic Crystal Ring Resonator

Abstract: A 2D hole-type hexagonal lattice photonic crystal is utilized, herein, to detect the refractive index change of the material infiltrated into the designed circular sensing area which also resembles a ring resonator. The accuracy of the detection process is enhanced considering the simultaneous shift of the resonance wavelengths and the intensity modulation which occur in two separate spectral regions. The presented structure has the ability to detect liquids, material concentrations in fluids and gases having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Thus, a low detection limit of ∼5.85 × 10 –5 RIU (1.49% in CO 2 concentration) is achieved in the current PF-MC sensor. The detailed comparison of the sensitivity with other optical RI-based gas sensors is summarized in Figure c. ,, A more comprehensive comparison of the CO 2 sensing performance of the typical reported sensors and the present work is summarized in Table . We should stress that the sensitivity of the PF-MC can compare favorably with plenty of other optical gas sensors in previous reports.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, a low detection limit of ∼5.85 × 10 –5 RIU (1.49% in CO 2 concentration) is achieved in the current PF-MC sensor. The detailed comparison of the sensitivity with other optical RI-based gas sensors is summarized in Figure c. ,, A more comprehensive comparison of the CO 2 sensing performance of the typical reported sensors and the present work is summarized in Table . We should stress that the sensitivity of the PF-MC can compare favorably with plenty of other optical gas sensors in previous reports.…”
Section: Resultsmentioning
confidence: 97%
“…Optical sensors based on refractive index (RI) change have become an alternative gas detection tool owing to their handheld capability and room-temperature operation. As promising candidates, optical fiber-based sensors , and whispering-gallery-mode (WGM) microcavity-based sensors were developed and applied in sensing the surrounding environment. Specifically, the WGM microcavity is a resonator that can confine light through resonance. The change of the RI of the surrounding medium influences resonance in the microcavity via the intermediate effect of the evanescent field, and the corresponding shift of the resonant wavelength is engaged as a probe to sense the environmental change. Especially, in the case of rolled-up microtubes, the microring-like cross section also acts as a WGM resonator, , while the subwavelength tube wall leads to an intensified evanescent field in the surrounding environment, and the enhanced coupling from the evanescent field greatly promotes the sensitivity in a large working range. ,,, The wide spectral range and the tubular geometry make it an ideal candidate for on-chip sensing devices, especially in an opto-fluidic system for real-time sensing of a tiny amount of sample .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated a very low LoD of PSi-based sensors, down to 10 -7 RIU [10,17], which has enabled the detection of biomolecules in a concentration range of interest for multiple biomedical applications [18,19]. It has also been proved that PSi-based RI sensors can reach sensitivities on the order of 10 3 nm/RIU, much higher than the ones that can be obtained with non-porous sensors with a similar Q-factor [10,20]. Besides, new techniques based on Tamm/Fano resonances promise to reach figures of merit (FOM) up to 10 3 RIU -1 with these structures [21].…”
Section: Introductionmentioning
confidence: 99%
“…When the optical mode propagates through the resonator, the resonant wavelength is influenced by the refractive index of the material surrounded by the resonator. Various structures to detect changes in the resonant wavelength have been introduced, such as disk resonators [1,2], Bragg gratings [3], photonic crystals [4,5], Mach–Zehnder interferometers [6], and ring resonators [7,8]. Recently, as applications have expanded to the biomedical field, many efforts have been made to reduce the sensor size.…”
Section: Introductionmentioning
confidence: 99%